Socio-economic impacts of bamboo enterprises in the Mid-hills of Nepal: A case study on Pahari community at Badikhel Village, Lalitpur - Bajracharya, M. Shakya; Rajbhandary, S.; Das, A. N. (Banko Janakari, 2013)
The present study investigates the associate enterprises involving bamboobased weaving and handicraft making at Badikhel Village Development Commitee, Lalitpur District, Central Nepal. It aims to assess the socio-economic importance of bamboo craft making on Pahari community at Badikhel. Forty households were randomly selected for questionnaire survey from the areas with higher density of bamboo entrepreneurship practiced. Perceived stakeholders were interviewed to examine their roles and to find out the contribution of bamboo enterprises to household income. Group discussions on issues of bamboo cultivation and management were conducted following RRA and PRA techniques. It was found that Badikhel impregnates four species of bamboo belonging to two genera viz. Bambusa and Drepanostachyum and are important and traditional source of livelihood for the Paharis, one of the ethnic groups in the study area. An average bamboo handicraft maker obtained NRs. 1000 to NRs. 5000 per month from the cash sales of assorted handicrafts. However, no significant bamboo management practices were carried out by the entrepreneurs. Three out of four community managed forests in the study area planted only Bambusa nepalensis as per local demand. Since stakeholders’ involvement in actual promotion of bamboo handicraft industry and bamboo management is meager there is an urgent need for the formation of a larger association of bamboo users for the growth and development of the bamboo entrepreneurship in the area. DOI: http://dx.doi.org/10.3126/banko.v22i2.9195 Banko Janakari: A Journal of Forestry Information for Nepal Vol. 22, No. 2, 2012 November Page: 11-18 Uploaded date: 12/1/2013